Is live high-train low altitude training relevant for elite athletes? Flawed analysis from inaccurate data - Millet, G. P.; Chapman, R. F.; Girard, O.; Brocherie, F. (British Journal of Sports Medicine, 2019)
To conclude, the statement that `altitude training does not convincingly increase exercise performance and should not be recommended to elite (endurance) athletes` is not supported by our analysis of the existing literature. We believe the assumption that athletes with already high Hbmass values do not increase their Hbmass after altitude training is flawed and biased by the inclusion of inaccurate data.